Pembuatan Aplikasi Berbasis Web Profile MTS Syekh Mubarok untuk Optimalisasi Layanan Informasi - Farid Zahran Wafi; Irwan Maulana; Rhafly Andika Tampati (CV. Multi Kreasi Media, 2025)
MTS Syekh Mubarok is one of the educational institutions located in Cisoka District, Tangerang Regency. Currently, the delivery of school-related information is still carried out conventionally through verbal communication or messaging applications like WhatsApp, which is less effective and efficient. In addition, the student registration process is still done manually. To address these issues, the authors developed a web-based information system that can be used to present the school profile and facilitate online student registration. This system was built using the Laravel and Bootstrap frameworks by adopting the waterfall software development method, which includes the stages of analysis, design, implementation, testing, and maintenance. The final result is a school profile website capable of delivering digital information to the public and supporting the student admission process without requiring them to visit the school in person.